2015
DOI: 10.1523/jneurosci.1034-15.2015
|View full text |Cite
|
Sign up to set email alerts
|

Neuronal Store-Operated Calcium Entry and Mushroom Spine Loss in Amyloid Precursor Protein Knock-In Mouse Model of Alzheimer's Disease

Abstract: Alzheimer's disease (AD) is the most common reason for elderly dementia in the world. We proposed that memory loss in AD is related to destabilization of mushroom postsynaptic spines involved in long-term memory storage. We demonstrated previously that stromal interaction molecule 2 (STIM2)-regulated neuronal store-operated calcium entry (nSOC) in postsynaptic spines play a key role in stability of mushroom spines by maintaining activity of synaptic Ca

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

14
195
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 164 publications
(212 citation statements)
references
References 37 publications
(8 reference statements)
14
195
0
Order By: Relevance
“…In contrast, stimulation of CamKII was not affected by removal of extracellular Ca 2ϩ but was fully abolished by using an endoplasmic reticulum Ca 2ϩ ATPase inhibitor. Importantly, mGluR5 activity is directly linked to endoplasmic reticulum Ca 2ϩ levels, which, in turn, regulate the expression of stromal interaction molecule 2 (STIM2) (41). STIM2 is an endoplasmic reticulum-localized protein that controls neuronal store-operated calcium entry (nSOC) and thereby regulates CamKII activity and stabilization of mushroom spines (42).…”
Section: Figure 7 Fyn Kinase Inhibition Prevents Activation Of Pyk2 mentioning
confidence: 99%
“…In contrast, stimulation of CamKII was not affected by removal of extracellular Ca 2ϩ but was fully abolished by using an endoplasmic reticulum Ca 2ϩ ATPase inhibitor. Importantly, mGluR5 activity is directly linked to endoplasmic reticulum Ca 2ϩ levels, which, in turn, regulate the expression of stromal interaction molecule 2 (STIM2) (41). STIM2 is an endoplasmic reticulum-localized protein that controls neuronal store-operated calcium entry (nSOC) and thereby regulates CamKII activity and stabilization of mushroom spines (42).…”
Section: Figure 7 Fyn Kinase Inhibition Prevents Activation Of Pyk2 mentioning
confidence: 99%
“…Indeed, CaN phosphatase activity is enhanced in aging neurons and plays an important role in increased long-term depression [24,25]. We observed that the STIM2-nSOC-CaMKII mushroom spine maintenance pathway is also disrupted in recently developed APP-KI mouse models of AD [26], in conditions of amyloid toxicity [27], in aging neurons and in sporadic AD brains [19]. Intriguingly, pharmacological or genetic rescuing of this pathway in KI mice restores mushroom spines as well as expression of synaptic proteins such as pCaMKII and postsynaptic density protein 95 [19,26,27].…”
mentioning
confidence: 80%
“…We observed that the STIM2-nSOC-CaMKII mushroom spine maintenance pathway is also disrupted in recently developed APP-KI mouse models of AD [26], in conditions of amyloid toxicity [27], in aging neurons and in sporadic AD brains [19]. Intriguingly, pharmacological or genetic rescuing of this pathway in KI mice restores mushroom spines as well as expression of synaptic proteins such as pCaMKII and postsynaptic density protein 95 [19,26,27]. Therefore, we think that the formation and stability of mushroom spines is regulated by the balance of CaMKII and CaN activity.…”
mentioning
confidence: 82%
“…Indeed, recent studies have detected the presence of Orai1 channels in central neurons, 1,2 and further studies indicated that STIM2, the sensor for endoplasmic reticulum calcium store depletion, is instrumental in maintenance of mature dendritic spines in cultured hippocampal neurons. 3,4 We have recently analyzed the role of Orai1 in dendritic spine formation and plasticity. This study follows our interest in the role of calcium stores in spine plasticity, where we found that dendritic spines contain ryanodine receptor-type calcium stores.…”
mentioning
confidence: 99%
“…Both of them are present in hippocampal neurons, in different concentrations and distribution. 6 The demonstration that STIM2 is important for spine maintenance, and that it is linked to presenilin, a pivotal molecule in the neurodegenerative Alzheimer disease, 3,4 re-assigns a key role for calcium homeostatic mechanisms in the development of AD. Further studies should clarify the relations among the different components of the SOCE channels, and their relevance to calcium stores and neurodegenerative diseases.…”
mentioning
confidence: 99%